Graphene Quantum Dot-TiO2 Photonic Crystal Films for Photocatalytic Applications - Maria-Athina Apostolaki; Alexia Toumazatou; Maria Antoniadou; Elias Sakellis; Evangelia Xenogiannopoulou; Spiros Gardelis; Nikos Boukos; Polycarpos Falaras; Athanasios Dimoulas; Vlassis Likodimos (Nanomaterials, 2020)
Photonic crystal structuring has emerged as an advanced method to enhance solar light harvesting by metal oxide photocatalysts along with rational compositional modifications of the materials’ properties. In this work, surface functionalization of TiO2 photonic crystals by blue luminescent graphene quantum dots (GQDs), n–π* band at ca. 350 nm, is demonstrated as a facile, environmental benign method to promote photocatalytic activity by the combination of slow photon-assisted light trapping with GQD-TiO2 interfacial electron transfer. TiO2 inverse opal films fabricated by the co-assembly of polymer colloidal spheres with a hydrolyzed titania precursor were post-modified by impregnation in aqueous GQDs suspension without any structural distortion. Photonic band gap engineering by varying the inverse opal macropore size resulted in selective performance enhancement for both salicylic acid photocatalytic degradation and photocurrent generation under UV–VIS and visible light, when red-edge slow photons overlapped with the composite’s absorption edge, whereas stop band reflection was attenuated by the strong UVA absorbance of the GQD-TiO2 photonic films. Photoelectrochemical and photoluminescence measurements indicated that the observed improvement, which surpassed similarly modified benchmark mesoporous P25 TiO2 films, was further assisted by GQDs electron acceptor action and visible light activation to a lesser extent, leading to highly efficient photocatalytic films.